2014
DOI: 10.1142/s0129183114410022
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann kinetic modeling and simulation of thermal liquid–vapor system

Abstract: We present a highly e±cient lattice Boltzmann (LB) kinetic model for thermal liquid-vapor system. Three key components are as below: (i) a discrete velocity model (DVM) by Kataoka et al. [Phys. Rev. E 69, 035701(R) (2004)]; (ii) a forcing term I i aiming to describe the interfacial stress and recover the van der Waals (VDW) equation of state (EOS) by Gonnella et al. [Phys. Rev. E 76, 036703 (2007)] and (iii) a Windowed Fast Fourier Transform (WFFT) scheme and its inverse by our group [Phys. Rev. E 84, 046715 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Moreover, the right column of Figure 17 revealed that the local maxima in the temperature profiles are located in the liquid-vapour interface regions. In these regions, where large density gradients are present, there is an unphysical heat generation process, due to the spurious velocity, a numerical effect that plagues the LB models [5,88,89,90,91,92,93,94,95,96,97]. This numerical effect has been succesfully reduced in this paper by using the fifth order weighted essentially non-oscillatory (WENO-5) numerical scheme.…”
Section: Phase Separation Dynamics Between Heat Extracting Parallel P...mentioning
confidence: 99%
“…Moreover, the right column of Figure 17 revealed that the local maxima in the temperature profiles are located in the liquid-vapour interface regions. In these regions, where large density gradients are present, there is an unphysical heat generation process, due to the spurious velocity, a numerical effect that plagues the LB models [5,88,89,90,91,92,93,94,95,96,97]. This numerical effect has been succesfully reduced in this paper by using the fifth order weighted essentially non-oscillatory (WENO-5) numerical scheme.…”
Section: Phase Separation Dynamics Between Heat Extracting Parallel P...mentioning
confidence: 99%
“…Distance concepts in the phase space or its sub-spaces are used to describe the difference and similarity of behavior. Up to now, DBM has been used in various multiphase flow systems, such as hydrodynamic instabilities [36,[40][41][42][43][44], compressible flows under impact [35][36][37][38], non-equilibrium combustion [45][46][47], non-equilibrium phase separation [48][49][50][51], and droplets collision [52]. For example, Gan, et al [48] used a DBM to study the Hydrodynamic Non-Equilibrium (HNE) and TNE effects in phase separation process.…”
Section: Introductionmentioning
confidence: 99%